2016
DOI: 10.1007/s00441-016-2407-9
|View full text |Cite
|
Sign up to set email alerts
|

αv integrins: key regulators of tissue fibrosis

Abstract: Chronic tissue injury with fibrosis results in the disruption of tissue architecture, organ dysfunction and eventual organ failure. Therefore, the development of effective anti-fibrotic therapies is urgently required. During fibrogenesis, complex interplay occurs between cellular and extracellular matrix components of the wound healing response. Integrins, a family of transmembrane cell adhesion molecules, play a key role in mediating intercellular and cell-matrix interactions. Thus, integrins provide a major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 55 publications
3
95
0
Order By: Relevance
“…Because the severity of NASH-induced liver fibrosis is the main predictor of liver-related mortality in NASH, (7) it is critically important to identify the mechanisms responsible for fibrosis development in NASH and to develop treatments that are effective in the prevention and reversal of fibrosis. Recently, RGD-binding integrins were found to play an important role in the development of organ fibrosis, (35) and several studies, including a study from our laboratory, demonstrated the efficacy of a potent small-molecule synthetic analog of the RGD peptide (CWHM-12) in mouse-injury models of liver, lung, muscle, and pancreatic fibrosis. (14,20,21) Here, by assessing CWHM-12 in a mouse model of NASH, we provide evidence supporting the role of RGD-binding integrins in the pathogenesis of NASH-induced liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Because the severity of NASH-induced liver fibrosis is the main predictor of liver-related mortality in NASH, (7) it is critically important to identify the mechanisms responsible for fibrosis development in NASH and to develop treatments that are effective in the prevention and reversal of fibrosis. Recently, RGD-binding integrins were found to play an important role in the development of organ fibrosis, (35) and several studies, including a study from our laboratory, demonstrated the efficacy of a potent small-molecule synthetic analog of the RGD peptide (CWHM-12) in mouse-injury models of liver, lung, muscle, and pancreatic fibrosis. (14,20,21) Here, by assessing CWHM-12 in a mouse model of NASH, we provide evidence supporting the role of RGD-binding integrins in the pathogenesis of NASH-induced liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…ASC treatment prevented BLM-induced upregulation of TNF-α expression in both lung and skin wound tissue (Table 1; p < 0.05). Expression of α v -integrin mRNA, a transmembrane cell adhesion molecule that modulates tissue fibrosis (Conroy, Kitto, & Henderson, 2016), was also increased in lung and skin from BLM-treated mice compared to saline controls (…”
Section: Molecular Markers Of Inflammation and Fibrosis Are Upregulmentioning
confidence: 99%
“…Integrins are the primary mechanosensors and transducers of tissue stiffness and several integrins have been identified as key drivers of profibrotic signaling in various organs. Some of these integrins, in particular αv subunit integrins, such as αvβ1 and αvβ6, have been shown to control the activation of latent TGF-β1 complex and targeting these integrins with small molecule inhibitors can block or reverse fibrosis progression in mouse models (Henderson and Sheppard, 2013; Henderson et al, 2013; Reed et al, 2015; Conroy et al, 2016). Given that BRD4 is critical for TGF-β-dependent profibrotic gene expression, BRD4 activity may be one of the downstream targets of integrin and TGF-β action.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%